Minimally invasive anatomic liver resection: Results of a survey of world experts. (15th December 2021) - Morimoto, Mamoru; Monden, Kazuteru; Wakabayashi, Taiga; Gotohda, Naoto; Abe, Yuta; Honda, Goro; Abu Hilal, Mohammed; Aoki, Takeshi; Asbun, Horacio J.; Berardi, Giammauro; Chan, Albert C.Y.; Chanwat, Rawisak; et al.
Abstract: Background: Although the number of minimally invasive liver resections (MILRs) has been steadily increasing in many institutions, minimally invasive anatomic liver resection (MIALR) remains a complicated procedure that has not been standardized. We present the results of a survey among expert liver surgeons as a benchmark for standardizing MIALR. Method: We administered this survey to 34 expert liver surgeons who routinely perform MIALR. The survey contained questions on personal experience with liver resection, inflow/outflow control methods, and identification techniques of intersegmental/sectional planes (IPs). Results: All 34 participants completed the survey; 24 experts (70%) had more than 11 years of experience with MILR, and over 80% of experts had performed over 100 open resections and MILRs each. Regarding the methods used for laparoscopic or robotic anatomic resection, the Glissonean approach (GA) was a more frequent procedure than the hilar approach (HA). Although hepatic veins were considered essential landmarks, the exposure methods varied. The top three techniques that the experts recommended for identifying IPs were creating a demarcation line, indocyanine green negative staining method, and intraoperative ultrasound. Conclusion: Minimally invasive anatomic liver resection remains a challenging procedure; however, a certain degree of consensus exists among expert liver surgeons. Abstract : Highlight Morimoto and colleagues summarized the opinions of the world's minimally invasive anatomic liver resection (MIALR) experts on detailed anatomical knowledge, landmarks, and techniques regarding inflow control and liver parenchymal resection with hepatic vein exposure. Although many challenges remain, these expert opinions will promote the spread and development of safe MIALR.